The Effectiveness of Using the Parallel Story Approach in Deepening the Islamic Identity in Schools of Karak Governorate - Mohammad Ali Al-Bayaydah (Budapest International Research and Critics University, 2023)
The study aimed to reveal the effectiveness of using the parallel story approach in deepening the Islamic identity in the schools of the Education Directorates in Karak Governorate. The sample of the study consisted of (87) students from the seventh grade who were randomly selected from one of the schools of the Directorate of Education in Karak during the first semester of the academic year 2022/2023. The parallel story approach was used in teaching the first experimental group, while the traditional method was used in teaching the students of the control group. To achieve the aim of the study, the tool prepared by the researcher was used, which is a test to find out the level of success in acquiring Islamic values, and four units of study were used from the Islamic Education curriculum for the seventh grade, and its contents were reformulated into four types of Islamic stories, taking into account the rules of writing the story. The study showed statistically significant differences at the level of (α = 0.05) between students' performance in imagination skills due to the teaching strategy used, in favor of the parallel story approach. It made a number of recommendations.